Strength and Durability Characteristics of Soil-Cutting Working Tools - D. A. Mironov; S. A. Sidorov; I. V. Liskin (Сельскохозяйственные машины и технологии, 2019)
The most important task in designing competitive agricultural machinery is the production of parts with long service life. The development of new technologies and materials determines the technical level of agricultural engineering. The plowshare blade is the most loaded and important part, as its parameters determine the quality, energy and economic indicators of the technological operation of plowing. (Research purpose) To determine and confi rm theoretically material and technological parameters of low quality level of domestic plowshares manufactured without the use of modern technologies. Then they analyze construction materials of plowshares and other parts of tillage implements produced by leading foreign companies, and come to a conclusion that lowand medium-carbon boron-containing alloyed and high-alloyed steels are used in their production. Leading global manufacturers of machine parts also often apply surface hardfacing with carbide coatings. (Results and discussion) The authors have theoretically and experimentally determined the directions of increasing the strength and durability of plowshare working tools. They have chosen basic materials for plowshares basing mainly on the strength parameters. They have conducted comparative laboratory tests of various materials and witness samples (including double-layer ones) for abrasive wear resistance on two bench installations; identifi ed materials for carbide coatings, clarifi ed the relative wear resistance coeffi cients of steel carbide layers recommended for use in the design of plowshares; and considered a technological method of hardening machine working tools. (Conclusions) The authors propose a simplifi ed computational procedure for selecting design and material parameters (thickness and width of hardening coatings) of plowshare blades and over-chisels, depending on the wear characteristics of the materials used and the plowshare thickness. They have stated mathematical relationships that determine the linear wear of plowshare blades and chisels depending on the characteristics of the materials used, design parameters, soil conditions and total operation time and carried out comparative operational and duration testing of newly developed plowshares. It has been shown that the marginal operating time of new products exceeds the duration indicators of serial counterparts in diff erent soil and climatic conditions in 3.5-5.5 times.